Модель электромагнитных помех УВЧ-усилителя мощности - Kudrya, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
An electrodynamically justified model of a balanced UHF-band power amplifier is proposed. The analysis of the amplifier was performed based on the systematic application of complex structure decomposition and calculations based on the analogy of plane and spheroparallel fields, which made it possible to account for electromagnetic interference from the communicator in the form of dependent sources of electrical energy. Their macro-models were developed in the MicroCap software environment, which made it possible to conduct a comparative evaluation of the frequency response.